Improving supply chain social responsibility through supplier development - Zhang, Min; Pawar, Kulwant S.; Bhardwaj, Saurabh (Taylor & Francis, 2017)
Corporate social responsibility (CSR) emphasises that the entire supply chain of a company should protect natural environment and contribute to social well-being in a tangible way. This study aims to clarify the effects of supplier development practices on supply chain social responsibility. The investigation uses a qualitative case study approach and empirically explores how to develop supplier’s CSR capabilities in a pharmaceutical supply chain. The results indicate that manufacturers can apply supplier development practices, including standard operating procedures (SOPs), audits, collaboration and training, to develop supply chain social responsibility. SOPs and audits are indirect supplier development practices that are designed in response to institutional pressures, and collaboration and training are direct supplier development practices that provide resources for bridging supplier’s CSR capability gaps. In addition, the indirect and direct supplier development practices positively influence each other and they are complementary in enhancing supply chain social responsibility.